Navigating health challenges: Singapore’s National University Health System’s approach to child and family well-being - Yee Keow Chiong; Wanyun Lin; Logan Manikam; Wei Ying Hai; Mat Shah; Jeannie Chiam; Mahesh Choolani; Yung Seng Lee (Annals, Academy of Medicine, Singapore)
Singapore’s progressive commitment to addressing child and family well-being is anchored in its forward-thinking public health agenda. Recognising that long-term population health outcomes are shaped by early-life interventions, Singapore has directed increasing attention towards addressing complex health challenges that emerge during childhood and across the family unit. These challenges are compounded by factors such as rapid urbanisation and rising cost of living, technological shifts and societal transitions that have exacerbated sedentary behaviours. With decreasing total fertility and birth rates, it is of utmost importance to realise each child’s maximum potential